2015
DOI: 10.1038/tp.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical expression of a newly identified splicing variant of the DLG1 gene in patients with early-onset schizophrenia

Abstract: The human discs, large homolog 1 gene (DLG1) is mapped to the schizophrenia-susceptibility locus 3q29, and it encodes a scaffold protein that interacts with the N-methyl-D-aspartate receptor presumably dysregulated in schizophrenia. In the current study, we have newly identified a splicing variant of DLG1, which is transcribed from an unreported 95-base-pair exon (exon 3b) and is labeled 3b(+). We investigated the mRNA expression of 3b(+) in the post-mortem dorsolateral prefrontal cortices of patients with psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
(40 reference statements)
2
22
0
Order By: Relevance
“…Considering that deletions in the 3q29 region occur at different break points in patients, resulting in deletions of varying number of genes in each case (Mulle et al, 2010;Pollazzon et al, 2009;Quintero-Rivera et al, 2010;Seo et al, 2010), it is possible that the multiple clinical features in this syndrome are synergistically caused by PAK2 and other genes in this region. This may be supported by a recent study, in which DLG1, another gene located in the 3q29 deletion region, was found to be involved in early-onset schizophrenia (Toyooka et al, 2002;Uezato et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Considering that deletions in the 3q29 region occur at different break points in patients, resulting in deletions of varying number of genes in each case (Mulle et al, 2010;Pollazzon et al, 2009;Quintero-Rivera et al, 2010;Seo et al, 2010), it is possible that the multiple clinical features in this syndrome are synergistically caused by PAK2 and other genes in this region. This may be supported by a recent study, in which DLG1, another gene located in the 3q29 deletion region, was found to be involved in early-onset schizophrenia (Toyooka et al, 2002;Uezato et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Generally, early-onset schizophrenia (EOS) is intractable and the prognosis is poor compared with non-early-onset schizophrenia (non-EOS). In addition, in our previous clinical genetic study in consideration of the onset age, gene expression related to glutamate neurotransmission was different between EOS and non-EOS [31]. Findings observed in these and our studies suggested that heterogeneity of the system related to glutamate neurotransmission appears as a differences in the onset age of schizophrenia and influences response to treatment.…”
Section: Discussionsupporting
confidence: 58%
“…Another study demonstrated increased expression of DLGAP1 in the nucleus accumbens [ 9 ]. Moreover, the expression level of DLG1 and DLG2 was also found to be significantly skewed in a schizophrenia rat model and in schizophrenic patients [ 32 , 96 98 ]. The deregulation of DLGs and DLGAP1 in these patients could be an indication of malfunction of NMDA receptors.…”
Section: Introductionmentioning
confidence: 99%